Bringing Up Mischievous Strips: The Katzenjammer Kids’ Domestication in Spanish and Italian Children’s Comics Magazines - Van de Wiele, Eva; Pintor Iranzo, Ivan (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2023)
This article examines how the comic series The Katzenjammer Kids, created by Rudolph Dirks in 1897 and whose main characters are two wicked children, has been usually altered, modified, and reframed due to its publication in Spain and Italy. By using the concept of domestication and utilizing tools of the history and formal analysis of comics and the contextual studies used in iconography, we try to study the influence and the afterlife impact of the forms, narratives, and gags of The Katzenjammer Kids and, at the same time, to provide a theoretical-methodological framework for understanding the cultural scope of these phenomena that characterize a field of study such as comics reception, which has been relatively underdeveloped.